Complicated streamer dynamics in petal‐like patterns formed on the substrate downstream of an argon plasma jet. Issue 9 (27th May 2022) - Wu, Kaiyue; Zhao, Na; Wu, Jiacun; Zhang, Furong; Niu, Mengyu; Ran, Junxia; Jia, Pengying; Li, Xuechen
Abstract: Streamer behaviors, related to discharge patterns, can determine the distribution of active species, which play an important role in the applications of the plasma jet. In this article, petal‐like patterns formed on the substrate are observed for the first time downstream of an argon plasma jet. The penta‐petalous pattern is taken as an example to discuss the pattern formation mechanism, which results from two positive discharges ( D p1 and D p2 ) and one negative discharge ( D n ) in every voltage cycle. Fast photography is implemented to reveal the complicated streamer dynamics of D p2 . Results indicate that D p2 with a low Q undergoes a stripe phase, a homogeneous phase, and a branch phase. The complicated streamer dynamics of D p2 are analyzed based on optical emission spectra. Abstract : Plasma plumes generated by free jets appear as distinctive morphologies resulting from different streamer behaviors, which determine the distribution of active species, hence play an important role in plasma jet applications. Similarly, patterns are formed on the substrate, which is inevitable in applications of plasma jets. In this article, a penta‐petalous pattern formed on the substrate is observed for the first time downstream of an argon plasma jet, which results from two positive discharges ( D p1 and D p2 ) and one negative discharge ( D n ) in every voltage cycle. Fast photography is implemented to reveal the complicated streamer dynamics of D p2 . Results indicate that D p2 undergoes a beginning stripe phase and a final branch phase, between which a homogeneous phase appears with a low Q .